Analisis Sistem Kemitraan Petani Penangkar dan PT. Pertani dengan PT. Citra Nusantara Mandiri - Fitri, Melani Anisa; Afrizal, Roni; Yuliandri, Yuliandri (Journal of Agribusiness and Community Empowerment, 2018)
The existence of PT. CNM Solok becomes very important as one of the guarantor of the availability of Indonesian corn seeds in order to keep corn production in a sustainable manner. In operation PT. CNM Solok in cooperation with PT. Pertani and farmer breeder. During the partnership there were two barriers: the delay in product distribution and the late payment of the contract. The purpose of this research is (1) Analyzing the partnership pattern applied by PT. CNM Solok with farmer breeders and PT. Pertani, (2) Analyze the evaluation of partnership implementation implemented by PT. CNM Solok with farmer breeders and PT. Pertani, (3) Compare the income level of the breeder farmer with regional income standard when partnering with PT. CNM Solok, (4) Describe the level of satisfaction of both partners of PT. CNM Solok is farmer breeders and PT. Pertani to the way the partnership so far.  This research was carried out for 2 months from the date of February 20, until May 19 2018 at PT. Citra Nusantara Mandiri Solok, Solok City, West Sumatra. The study used primary data (interviews and contract documents of partnership) and secondary data were processed descriptively qualitative. Partnership pattern of PT. CNM Solok with farmer breeder ie plasma core. While the partnership pattern of PT. CNM Solok with PT. Pertani is subcontracted. The implementation of the partnership has not been fully realized. Farmers income is lower than UMP with a land area of 0.25 hectares. Partners have been satisfied with existing partnerships